Heritage Trails and Cycling Tourism in City Branding: Exploring the Nexus of Experiences and Expectations - Prastyadewi, Made Ika; Nursanty, Eko; Pramandari, Putu Yusi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This paper delves into the intricate relationship between heritage trails and cycling tourism, specifically focusing on the case study of the heritage-rich city of Surakarta. The convergence of heritage trails and cycling tourism forms a dynamic nexus that influences both the experiences of tourists and their expectations. The notion of the "tourist gaze" serves as a foundational framework, shedding light on tourists' perceptions and anticipations of Surakarta's cultural heritage, culinary offerings, and local populace. Rooted in socially constructed constructs, the tourist gaze significantly shapes how tourists interpret and emotionally engage with Surakarta as a destination. Through a qualitative exploratory approach, this study delves into the multifaceted interplay between heritage trails, cycling experiences, and the tourist gaze. Data is derived from in-depth interviews with tourists engaging in heritage cycling trails, capturing their subjective accounts of experiences and expectations. The findings unveil a range of themes, including the influence of heritage sites on cyclists' emotional connection with the city, the role of the tourist gaze in framing their encounters, and the impact of well-designed heritage trails on overall satisfaction. The study not only advances our understanding of the complex interrelationship between heritage trails, cycling tourism, and the tourist gaze, but also offers practical insights for heritage site management, urban planning, and tourism experience enhancement in Surakarta and beyond.